2012
DOI: 10.1111/j.1467-789x.2012.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbial adaptation to dietary consumption of fructose, artificial sweeteners and sugar alcohols: implications for host–microbe interactions contributing to obesity

Abstract: The Western diet, comprised of highly refined carbohydrates and fat but reduced complex plant polysaccharides, has been attributed to the prevalence of obesity. A concomitant rise in the consumption of fructose and sugar substitutes such as sugar alcohols, artificial sweeteners, even rare sugars, has mirrored this trend, as both probable contributor and solution to the epidemic. Acknowledgement of the gut microbiota as a factor involved in obesity has sparked much controversy as to the cause and consequence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 99 publications
8
131
0
3
Order By: Relevance
“…Prior research also found an association of artificial sweeteners with both metabolic dysfunction (26,27) and weight gain (28)(29)(30), but these studies were based on consumption and the conclusions are likely to be affected by both confounding and reverse causality (persons already gaining weight choose to consume artificially sweetened beverages to prevent further weight gain). The biological mechanisms for the association between artificial sweetener and weight gain are proposed to relate to gut microbiota metabolism (31). Several recent studies of erythritol loading reported no effect on glucose (32,33), consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Prior research also found an association of artificial sweeteners with both metabolic dysfunction (26,27) and weight gain (28)(29)(30), but these studies were based on consumption and the conclusions are likely to be affected by both confounding and reverse causality (persons already gaining weight choose to consume artificially sweetened beverages to prevent further weight gain). The biological mechanisms for the association between artificial sweetener and weight gain are proposed to relate to gut microbiota metabolism (31). Several recent studies of erythritol loading reported no effect on glucose (32,33), consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding UC In vivo, fructose has been demonstrated to increase intestinal permeability, 49 stimulate the production of reactive oxygen species (ROS) and initiate pro-inflammatory processes. [50][51][52] Alterations in the microbiota composition associated with sugar intake have been described. Artificial sweeteners could induce compositional and functional alterations of the intestinal microbiota that promote glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…The normoxia and intermittent hypoxia groups could be classified into entrerotypes 1 and 2 given their relative enrichment in Bacteroides and Prevotella, respectively, and the significant increase in the abundance of Desulfovibrio in the intermittent hypoxia microbiomes [22]. The co-occurrence of Prevotella and Desulfovibrio found in the intermittent hypoxia group suggests evolution of a mucin-degrading niche whereby the sulfate liberated during Prevotella-mediated mucin degradation is removed by Desulfovibrio, a process required to prevent sulfate inhibition of mucin degradation [22,23]. Mucin degradation by bacteria is often regarded as an initial stage in pathogenesis, since it would disturb the protection of the host mucosal surfaces.…”
Section: Discussionmentioning
confidence: 99%